Hubungan antara Tingkat Kecemasan dengan Kejadian Dismenorea pada Remaja Putri Kelas VII di SMPN 1 Ciwidey Kabupaten Bandung - Eti Sukmiati; Khairunnisa V (STIKes Karsa Husada Garut, 2017)
One of the factors that influence adolescent dysmenorrhoea is anxiety. Adolescents who experience anxiety will increase the occurrence of dysmenorrhea.Dysmenorrhea is a menstrual disorder that is most often complained of pain before or after menstruation.This study aims to get the relationship between the level of anxiety with the incidence of dysmenorrhea in SMPN 1 Ciwidey students.This research is an analytic research correlation with cross sectional design.Population in this study were students of SMPN 1 Ciwidey class VII which amounted to 258 people. The number of samples in this study was 72 people using random sampling technique. The results of research at SMPN 1 Ciwidey showed there was a relationship between the level of anxiety with the incidence of dysmenorrhea with P-value = 0,000 (<0,005). This study concluded that there is a significant relationship between teenage anxiety with the incidence of dysmenorrhea in female students. It is hoped the school can optimize and provide counseling about dysmenorrhea to reduce anxiety levels.